SISTEM ANTI KORUPSI: SUATU STUDI KOMPARATIF DI INDONESIA, HONGKONG, SINGAPURA DAN THAILAND - Anita Carolina (Universitas Trunojoyo Madura, 2012)
This study is designed to cast light on the issue of corruption from diverse viewpoints, which is so deeply rooted in every aspect of life these days. Anti-corruption approaches on the part of the government are not expected to be so successful because the problem is too complicated. That is why appropriate comprehension of the issue is required first. This study explores the anti-corruption and corruption-preventive systems in Asia, especially in Singapore, Hong Kong, Thailand and Indonesia. Moreover, this study compares how those countries combat corruption with the aim of ascertaining why Singapore and Hong Kong are more effective in curbing corruption than Thailand and Indonesia. Singapore, Hong Kong, Thailand and Indonesia have relied on a single anti-corruption agency (ACA) to implement the anti-corruption laws. This study concludes that the critical difference between success and failure in combating corruption in Asian countries is the political will of the government. Singapore and Hong Kong are more effective in corruption control because their governments have demonstrated their commitment by enforcing the comprehensive anticorruption laws impartially and providing the CPIB and ICAC with adequate personnel and budget to enable them to perform their functions effectively. In contrast, Thailand and Indonesia are less effective in curbing corruption because their governments lack the political will as reflected in the higher staff-population ratios and lower per capita expenditures of their ACAs and the selective enforcement of the anti-corruption laws. In addition to political will, the favourable policy contexts of Singapore and Hong Kong have enhanced the effectiveness of the CPIB and ICAC. On the other hand, the unfavourable policy contexts of Thailand and Indonesia have hindered the effectiveness of their ACAs.